Pergeseran Permainan Tradisional Di Kota Makassar - Hasruddin Nur; Muhammad Ferdhy Asdana (Phinisi Integration Review, 2020)
This study aims to describe the existence of traditional games in Tamalate Sub-District of Makassar City, how the children play life today and the reasons for the community especially children to choose modern games rather than traditional games. The data obtained in this study were analyzed using qualitative description analysis with stages reducing data, displaying data, and drawing conclusions. Data collection techniques used are observation, interviews, and documentation. The results showed that 1) The existence of traditional games in the Tamalate Sub-district of Makassar City was getting eroded, because traditional games as an escape when saturated, the lack of parental supervision and modern games were more interesting. 2) Children's play life in Tamalate Sub-district, Makassar City, which is modern play life with many Smartphones, Children are starting to leave traditional games. 3) The reason people especially children choose modern games, namely the existence of shame and prestige, environmental factors, lack of playing ground for children.